The type of COVID−19 vaccination does not affect reproductive function and pregnancy outcomes in infertile couples - Wang, Shiming; Wang, Ningning; Yao, Guidong; Su, Yingchun; Qi, Lin (Frontiers in Endocrinology, 2024)
Introduction: Studies on the effect of vaccine type and two other vaccines other than inactivated vaccines approved in China on in vitro fertilization (IVF) pregnancy outcomes are rare. To complement and confirm the existing findings, this research aimed to investigate whether there are adverse effects of different vaccine types in females and males on reproductive function and clinical pregnancy. Methods: This retrospective study enrolled 6,455 fresh embryo transfer cycles at the First Affiliated Hospital of Zhengzhou University between May 1, 2021, and October 31, 2022. The primary outcome is the clinical pregnancy rate (CPR). At the same time, the secondary results are the number of oocytes retrieved, two pronuclei (2PN) rate, blastocyst formation rate, high-quality blastocyst rate, and semen parameters (volume, density, sperm count, forward motility rate, total motility rate, immobility rate, and DNA fragment index (DFI) rate).Results: In the comparison of ovarian stimulation indicators, no statistically significant differences (P > 0.05) were found in Gn days, endometrial thickness, 2PN rate, metaphase 2 (MII) rate, high-quality embryo rate, and blastocyst formation rate. No significant differences (P>0.05) were found in age, body mass index (BMI), education level, and semen parameters (volume, density, sperm count, forward motility rate, total motility rate, immobility rate, and DFI rate) in these four groups.The multivariate regression model showed that neither the types of vaccines nor the vaccination status of both infertile couples significantly affected clinical pregnancy.The type of vaccine does not appear to have an unfavorable effect on ovarian stimulation, embryo development, semen parameters, and clinical pregnancy.